Measurement of the Q2, x and W2 dependence of single hadron production in deep inelastic muon scattering - Aubert, J; Bassompierre, G; Becks, K; Best, C; Böhm, E; de Bouard, X; Brasse, F; Broll, C; Brown, S; Carr, J; Clifft, R; Cobb, J; et al. (1982)
Measurements are presented of the distributions in scaled energy of the hadrons produced in high energy muon scattering. The observed dependence on x (non-factorisation) and Q2 (scaling violation) is similar to that expected from next to leading order QCD calculations. These variations in the data can be equivalently represented by a dependence on the single variable W2. © 1982.